Psychosocial outcomes following spinal cord injury in Iran. (May 2014) - Khazaeipour, Zahra; Norouzi-Javidan, Abbas; Kaveh, Mahboobeh; Khanzadeh Mehrabani, Fatemeh; Kazazi, Elham; Emami-Razavi, Seyed-Hasan
Abstract : Objective/background: In patients with spinal cord injury (SCI), SCI causes psychosocial complications that vary based on culture, conditions, and the amenities of each community. Health planners and social services should have full knowledge of these issues in order to plan schedules that address them. In this study, we aimed to understand the psychosocial problems of persons with SCI in Iran and to explore the requirements for minimizing these difficulties. Design: This was a descriptive cross-sectional study. Setting: Brain and Spinal Cord Injury Research (BASIR) Center, Tehran University of Medical Sciences, Tehran, Iran. Participants: One hundred nineteen persons with SCI referred to BASIR clinic to receive outpatient rehabilitation. Methods: In this study, trained interviewers administered a questionnaire to the participants. The questionnaire consisted of socio-demographic variables and psychosocial questions about finances, employment, housing, education, and social communication problems. Results: Psychosocial problems for persons with SCI are mainly associated with financial hardship due to unemployment and the high cost of living, followed by difficulties with transportation, house modification, education, marriage, social communication, sports, and entertainment. Psychological problems include sadness, depression, irritability/anger, suicidal thoughts, and a lack of self-confidence. The levels of the aforementioned problems differ with respect to sex. Conclusion: Persons suffering from SCI can face some serious psychosocial problems that may vary according to sex. For example, transportation difficulties can lead to problems such as unsociability. After recognizing these problems, the next step would be providing services to facilitate a productive lifestyle, enhancing social communication and psychological health, and ultimately creating a higher quality of life.